Biliary Rhabdomyosarcoma in Pediatric Patients: A Systematic Review and Meta-Analysis of Individual Patient Data - Fuchs, Juri; Murtha-Lemekhova, Anastasia; Kessler, Markus; Günther, Patrick; Fichtner, Alexander; Pfeiffenberger, Jan; Probst, Pascal; Hoffmann, Katrin (Frontiers in Oncology, 2021)
Background The biliary tree is a rare location of pediatric rhabdomyosarcoma. Due to the low incidence, there is a lack of evidence concerning therapeutic guidelines for this tumor location. In particular, the impact of surgery is discussed controversially. Purpose Objective is to generate evidence-based treatment guidelines for pediatric biliary rhabdomyosarcoma (BRMS). All available published data on therapeutic regimens and important prognostic factors are investigated with a focus on the role of surgery. Methods A systematic literature search of MEDLINE, Web of Science, and CENTRAL was performed. Patient data were entered individually. Data was pooled and qualitative and quantitative analyses of demographic data, therapy, postoperative/interventional outcomes, relapse, and survival were conducted. In an individual patient data analysis, cox regression was applied to identify key factors predicting the outcome of patients with BRMS. Results 65 studies met the inclusion criteria, providing data on 176 patients with BRMS. Individual patient data analysis showed a 5-year overall survival and progression-free survival of 51% and 50% for the total study population. For patients treated after 2000, 5-year OS and PFS was 65% and 59%, respectively. Absence of surgical tumor resection was an independent risk factor for death (Hazard ratio 8.9, 95%-CI 1.8-43.6, p = 0.007) and significantly associated with recurrent disease and disease-related death. Conclusion This analysis provides comprehensive information on the largest number of patients hitherto reported in the literature. BRMS is still associated with high morbidity and mortality. Surgical tumor resection is essential for appropriate oncological treatment of BRMS. International cooperation studies are needed to enhance evidence and improve the outcome of this orphan disease. Protocol Registration PROSPERO (CRD42021228911) https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021228911.